The potential of N2-modified cap analogues for precise genetic manipulation through mRNA engineering - Kurpiejewski, Karol; Stankiewicz-Drogon, Anna; Piecyk, Karolina; Rajkowska, Eliza; Skrzypczyk, Paulina; Geng, Jingping; Darzynkiewicz, Edward; Grzela, Renata; Jankowska-Anyszka, Marzena (Frontiers in Molecular Biosciences, 2024)
The technology of mRNA-based drugs is currently being intensively developed and implemented. Medical products of this type are already being used as viral vaccines and could potentially find application in a wide range of diseases. The tremendous interest in mRNA is due to the relatively easy production process, which can be quickly adapted to meet societal needs. The properties of this molecule depend on the structure of its individual components, such as the structure of the cap at the 5ʹ end. Modifications of the cap significantly affect the translational potential and lifespan of the whole mRNA. In the current work, we present the synthesis of derivatives of cap analogues modified at the N2 position of 7-methylguanosine. In addition to the substituent at the N2 position, the derivatives had either an extended triphosphate chain, a thiophosphate modification, an added cap1-modified nucleotide or an extended linker between the substituent and 7-methylguanosine. The compounds were tested for use as translation inhibitors and as components for mRNA preparation and appeared of interest for both applications.